Challenges of LNG (Liquefied Natural Gas) Carriers in 21' Century - Zanne, Marina; Grčić, Mirjana (Promet - Traffic&Transportation, 2009)
Natural gas is relatively cheap, environmentally friendlyand energetically efficient fossil fuel that is gaining in attractivenessdaily as it can be used in many sectors. As not all consumerscan be reached by pipelines the technique of transp01tingnatural gas in the liquefied form has been developed at the beginningof 20th century but it was only in 1959 that the firstoverseas transport of liquefied natural gas ( LN G) occurred. Inthe fifty years of operation LNG shipping has shown immaculatesafety records. LNG tankers can be described only in superlatives;they are without any doubt the most sophisticated and·expensive ships that sail around the globe, they demand specialattention when navigating to or out of harbours and need to bemanned with the most educated and experienced crew. LNGmarket is expanding and changing; demand is surpassing theproductivity, new importing and exporting countries appear,LNG fleet is growing in capacity and number at high pace, exploitationcontracts for the ships are being modified giving theopportunity for new companies to enter( . .. ). The paper givesan overview on liquefied natural gas market and the historic developmentof LNG shipping. It focuses on the recent boom inLNG shipping and emphasises questions concerning the safety,crewing and exploitation of the LNG tankers in the future.